2007
DOI: 10.1021/jf063472r
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Stability of Citral and Limonene in Sodium Dodecyl Sulfate−Chitosan and Gum Arabic-Stabilized Oil-in-Water Emulsions

Abstract: Citral and limonene are the major flavor components of citrus oils. Both of these compounds can undergo chemical degradation leading to loss of flavor and the formation of undesirable off-flavors. Engineering the interface of emulsion droplets with emulsifiers that inhibit chemical reactions could provide a novel technique to stabilize citral and limonene. At present, emulsified flavor oils are usually stabilized by gum arabic (GA), which is a naturally occurring polysaccharide-protein complex. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 31 publications
2
74
1
1
Order By: Relevance
“…It consists mainly of a mixture of arabinogalactan (AG) (80-90 % of the total gum in weight), glycoprotein (GP) (2-4 % of the total gum in weight) and arabinogalactan protein (AGP) (10-20 % of the total gum in weight) fractions (Bouyer et al 2011). Previous studies showed that gum arabic was widely used in preparation of emulsions, and the droplet characteristics were then evaluated (Jayme et al 1999;Djordjevic et al 2007Djordjevic et al , 2008Karaiskou et al 2008;Padala et al 2009;Bouyer et al 2011;Charoen et al 2011;Zhang and Liu 2011). However, no information is available concerning the effect of antioxidants on the stability of β-carotene in the emulsions stabilized by gum arabic.…”
Section: Effects Of Antioxidants On the Droplet Characteristics Of β-mentioning
confidence: 99%
“…It consists mainly of a mixture of arabinogalactan (AG) (80-90 % of the total gum in weight), glycoprotein (GP) (2-4 % of the total gum in weight) and arabinogalactan protein (AGP) (10-20 % of the total gum in weight) fractions (Bouyer et al 2011). Previous studies showed that gum arabic was widely used in preparation of emulsions, and the droplet characteristics were then evaluated (Jayme et al 1999;Djordjevic et al 2007Djordjevic et al , 2008Karaiskou et al 2008;Padala et al 2009;Bouyer et al 2011;Charoen et al 2011;Zhang and Liu 2011). However, no information is available concerning the effect of antioxidants on the stability of β-carotene in the emulsions stabilized by gum arabic.…”
Section: Effects Of Antioxidants On the Droplet Characteristics Of β-mentioning
confidence: 99%
“…After washing twice with distilled water, the dispersion of the encapsulates improved the aroma released out of dried microcapsules within a few hours (depending on the temperature). Djordjevic et al (2007) examined whether citral and limonene were more stable in emulsions stabilized with a sodium dodecyl sulfate (SDS)-chitosan complex than with gum arabic (GAR). Citral degraded less in GAR-stabilized emulsions than in SDS-chitosan-stabilized emulsions at pH 3.0.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…2,3,6,[10][11][12] In addition, multilayer emulsions may also be used to encapsulate oils and protect them from chemical deterioration, e.g., oxidation. [13][14][15] Chitosan has been shown to be a particularly effective biopolymer for coating the oil droplets in multilayer emulsions because of its unique functional attributes, natural abundance, and cationic character. 2,6,8,10,[13][14][15][16][17] Nevertheless, there is some concern that chitosan may interfere with lipid digestion and absorption, which could decrease the bioavailability of lipophilic nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Chitosan has been shown to be a particularly effective biopolymer for coating the oil droplets in multilayer emulsions because of its unique functional attributes, natural abundance, and cationic character. 2,6,8,10,[13][14][15][16][17] Nevertheless, there is some concern that chitosan may interfere with lipid digestion and absorption, which could decrease the bioavailability of lipophilic nutrients. Some studies suggest that lipid digestion and absorption is not affected by chitosan, [18][19][20] whereas others suggest that it is.…”
Section: Introductionmentioning
confidence: 99%